Creation, optimization and verification of a three dimensional numerical model to simulate a dragline bucket during the digging cycle using modern DEM software - Dymond, Graeme Francois Dryden (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2007.